TUM LONGAS CONDIMUS ILIADAS: THE PROPERTIUS’ HELEN - Martins, Paulo (Revista Archai, 2017)
This paper analyses the uses of the poetic image of Helen in Propertius, especially focusing on the metaphor: “Cynthia is Helen”. Cynthia can be understood both as lover of the ego-Propertius who emerges from poetic narratives as well as a metaphor for the poetry of Propertius, so my question is: how can Helen be associated with these two interpretations of Cynthia? I will suggest two possibilities: first, as a lover, Cynthia can be compared with Helen in beauty, impudence or infidelity. Secondly, as a metaphor for poetry, or as a book of elegies ”“ scripta puella ”“, Cynthia can be associated with the painting of Helen by Zeuxis in Croton, whose main features are beauty and perfection according to both Cicero (De Inuentione) and Dionysius of Halicarnassus (De Imitatione)